A survey on trends in outsourcing practices in Indian manufacturing organisations. Issue 6 (5th May 2009) - Singh, Amar; Narain, Rakesh; Yadav, R.C.
Outsourcing provides a means to adequately address the issues arising from intense global competition and market needs. Issues that need maximum attention are customer-focused strategies, economising on costs, accessing technological advancement, innovation, attainment of total quality in products, process and services, etc. A postal survey of 54 Indian manufacturing organisations has been carried out to ascertain aspects related to outsourcing such as reasons for outsourcing, currently outsourced processes, criterion for supplier selection, etc. The global trends in outsourcing and its impact on India are also discussed. The findings suggest that Indian organisations are vigorously pursuing outsourcing and have attracted world attention towards itself by providing products and services at most competitive prices.